(untitled) (Revista LIDER, 2021)
Despite the decrease in the poverty rate in Chile during the last 30 years, the so-called Chilean model has generated marked structural gaps between territories, which indicates that development has only reached some places in the geography. In the case of forest regions, the relationship between economic development and growth of large forestry has been in doubt in the last decade, which has led to the classification of the forest sector as an extractive sector, despite its status as a renewable resource. The foregoing has motivated the configuration of various stories referring to the territory, which range from the rejection of the forest sector to the negotiation and acceptance of it. This article proposes to explore the different territorialities existing in ten forest municipalities of the central-southern region of Chile, using a qualitative method through the use of grounded theory, where the analysis of sustainability reports of the forest companies Arauco and CMPC with the application of 17 semi-structured interviews with relevant actors of the territory (militants of the Mapuche movement, public affairs managers of Arauco and CMPC and civil society actors). The results show that three territorialities are constituted, which dispute the meanings associated with the territory: a hegemonic territoriality, expressed in the large forestry company, which has modified its discursive practices in order to obtain social legitimacy in the territories where it is established; subaltern territorialities that question the hegemonic discourse, fundamentally expressed in the Mapuche movement and, to a lesser extent, in the productive sectors displaced by the large forestry company. These last territorialities, within their heterogeneity, vary from open opposition to dialogue and acceptance, often depending on the situation.